Therapeutisches Vorgehen beim oligometastasierten Magen- und Ösophaguskarzinom - Schmidt, Thomas; Mönig, Stefan Paul (Der Chirurg, 2017)
The therapeutic approach to patients with oligometastatic gastric cancer and esophageal cancer is currently undergoing a shift towards a more aggressive therapy including surgical resection. In the current German S3 guidelines surgical treatment of metastatic disease is not recommended; however, nowadays interdisciplinary tumor boards have to evaluate such patients increasingly more often. On an individual basis a radical surgical resection of the primary tumor and the metastases is considered and performed in patients who respond well to multimodal chemotherapy concepts. In this review article the currently available data from the literature are discussed and a foundation for individually extended surgical approaches is presented. Together with the currently available results of the FLOT 3 study and the mostly retrospective studies, it seems to be possible to identify patients who would profit from such an aggressive treatment. In the future randomized prospective studies, such as the RENAISSANCE/FLOT 5 study and the GASTRIPEC study will have to evaluate whether an aggressive surgical therapy within multimodal therapy concepts of metastatic gastric and esophageal carcinomas is warranted.
Gesehen am 04.06.2018